MOVEMENT BEHAVIOURS OF PRESCHOOL CHILDREN IN BOSNIA AND HERZEGOVINA - Užičanin, Edin; Džibrić, Dževad; Đug, Muris; Babajić, Fuad; Huremović, Tarik; Nožinović Mujanović, Amra; Mujanović, Edin; Hodžić, Sanjin; Bilalić, Jasmin; Atiković, Almir (Sport - nauka i praksa, 2023)
The World Health Organization (WHO) released guidelines for physical activity, sedentary behaviour, and sleep for children under 5 years of age in 2019. In response to these guidelines, this study aimed to determine the proportion of preschool children (ages 3-5 years) who met the WHO guidelines. The time spent in physical activity, sedentary behaviour and sleep were objectively measured using accelerometer (ActiGraph wGT3x-BT). Screen time and sleep quality were assessed via parent questionnaire. Focus groups were conducted with parents and childcare staff to determine the feasibility of the protocol. The results showed that only 23% of the children met all three guidelines, and compliance rates varied for each guideline. The physical activity time guideline was met by 64% of children, the sleep duration guideline was met by 74% of children, and the screen time guideline was met by 53% of children. Only a low proportion of children met the WHO guidelines. The methods and devices used in this pilot study proved to be feasible and this has paved the way to conduct the main SUNRISE study in Bosnia and Herzegovina.
Keywords: movement behaviours; preschool children; screen time; sleep; sedentary behaviour